Safety and reliability issues when studying power structure fatigue in aviation and space engineering - M. A. Krasnenkov; C. I. Korshakovskiy; N. S. Chekalkin (Научный вестник МГТУ ГА, 2016)
The analysis of failures for the unit components has been presented in the paper. Specifying the possible failure of technical object components and units under operation that can cause catastrophic consequences and basing on statistics the authors have offered the estimation criteria for anthropogenic risk measure.